Analysis of the Effects of Post-2008 Anti-crisis Mild Monetary Policy of the Federal Reserve Bank and the European Central Bank - Dariusz Prokopowicz (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2020)
Since the emergence of the global financial crisis, a decade of time has passed, which allowed for a number of analyzes aimed at assessing government intervention programs of anti-crisis activities to rescue key economic entities from financial bankruptcy and to stimulate demand, investment and production as well as liquidity in the credit market . Currently, taking into account successful intervention in this area in the American economy, the result of these assessments is easy to predict. As part of the pro-development activities of the state intervention, the Federal Reserve Bank applied a low monetary policy of low interest rates and a program for activating lending and maintaining liquidity in the financial system by financing the purchase of the most endangered assets from commercial banks. A few years later, the European Central Bank applied the same activities of activation monetary policy. Currently, among economists prevails the view that if it were not for the application of rapid state intervention referring to the Keynesian formula from 1930s, the scale of the economic slowdown in the world and individual countries would be much greater.